UPDATES ON REHABILITATION AND PHYSICAL THERAPY INTERVENTIONS FOR INDIVIDUALS WITH SPINAL CORD INJURY (Vietnam Journal of Community Medicine, 2026)
Objectives: Spinal cord injury causes impaired mobility. This review aims to update physical therapy and rehabilitation interventions that can improve motor function in individuals with spinal cord injury.Method: A literature review was conducted using databases: PubMed, ScienceDirect and Google Scholar; keywords included: spinal cord injury, rehabilitation, physical therapy, contracture prevention, shoulder pain, wheelchair skills, aerobic training.Results: Effective interventions including assessment and training of wheelchair mobility skills, prevention of shoulder pain and contractures, muscle strengthening, aerobic endurance training, and fall prevention. The use of standardized assessment tools allow individualized rehabilitation goals.Conclusion: Physiotherapy interventions enhance funcitonal recovery for individuals with spinal cord injury. Rehabilitation programs should be individualized based on clinical assessment and scientific evidence to optimize functional performance and participation.
Keywords: Spinal cord injury, physical therapy, contracture, shoulder pain, wheelchair, cardiopulmonary endurance.